Evaluation of Exserohilum Prolatum as a Potential Mycoherbicide for Different Biotypes of Itchgrass (Rottboellia Cochinchinensis (Lour) Clayton) - Mahmoud Alloub, Hala Eltahir (2006)
Itchgrass or Rottboellia cochinchinensis is a noxious and widely spread annual grass weed in the tropics and subtropics. In Malaysia itchgrass is a major problem in the sugarcane plantations in the states of Perlis and Kedah. Preliminary and extended glasshouse experiments were conducted to classify itchgrass present in Peninsular Malaysia based on morphological characteristics to aid in its biological control. The results categorized 13 populations, collected from six infested states, into three biotypes. Biotype 1 found in association with banana, cocoa and oil palm or along the roadsides in Johor, Pahang and Perak. Biotype 2 found in association with maize, upland rice, rubber, sugarcane and tobacco in Kedah, Perlis and Selangor. Biotype 3 was found only along roadsides of Padang Kartong. Fungi associated with itchgrass were isolated from diseased plants collected from 14 different infested locations. Ten fungi were pathogenic to the three itchgrass biotypes. 4 Primary screening of the fungi showed that isolates of Botryodiplodia theobrome, Curvularia eragrostidis, C. fallax, C. lunata, C. pallescens and Fusarium oxysporum were highly pathogenic to most of the plants tested. Isolates of Exserohilum longirostratum, E. prolatum, Fusarium moniliforme and a Phoma sp. showed some degree of specificity to itchgrass. Further screening of E. prolatum against 32 plants belonging to 12 families showed complete kill of itchgrass, while all other plants tested were immune, resistant or tolerant to the isolate. Factors affecting the efficacy of E. prolatum were studied. Fungal growth and sporulation were evaluated in five culture media under three light durations. Highest colony diameters were obtained with CMA, PDA and CMA under the 12 hr light, however highest spore concentration was obtained with V8A under 24 hr light. Different additives were also evaluated for E. prolatum spore viability. The additives include suspensions of conidia in distilled water, conidia in three different concentrations of Tween 20 surfactant, conidia in three different palm oil concentrations, three combinations of Tween 20 concentrations and palm oil and conidia in five different concentrations of two herbicides glyphosate (Round Up®) and ammonium glufosinate (Basta 15®). The results showed high spore viability with Tween 20 and palm oil suspensions. However, both the herbicides greatly reduced fungal viability compared to the control. Factors affecting E. prolatum disease development were also studied. The results showed that increasing spore concentration increased disease severity, optimum wetness 5 duration was 24 hr, combination of surfactant and palm oil increased disease severity and reduced dry weight under 8 and 12 hr wetness duration and disease severity decreased with increasing plant age. The potential of E. prolatum as a mycoherbicide was evaluated under natural conditions in two field experiments in a non crop situation and in association with a maize crop. Application frequency and inoculum concentration greatly influence itchgrass control. Three application frequencies had significantly higher percentage of control compared to single and double applications. Within the three frequencies of application, increasing inoculum concentration increased itchgrass control compared to untreated check. The results indicate that E. prolatum has a good potential as a biocontrol agent for itchgrass.